The ALARP principle in process safety. Issue 1 (24th April 2013) - Baybutt, Paul
<x xml:space="preserve">Abstract</x> The principle that the risks for a facility should be reduced to As Low As Reasonably Practicable (ALARP) increasingly is embraced around the world. This article describes how the principle can be used to establish both individual and group risk tolerance criteria that are needed for risk analysis studies using techniques such as Layers of Protection Analysis. The consideration of uncertainties in risk estimates in the ALARP context and the use of the precautionary principle are also described, and the use of cost–benefit analysis in applying the ALARP principle is discussed. Other related principles used in risk management are described. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 36–40, 2014